An Analysis on the Subject-Verb Agreement Errors in Speaking Performance Made by the Second Year Students of English Department Students of UNP - Rizkiah Nadiroh Nasution; Zul Amri (Universitas Negeri Padang, 2021)
This research aimed at identifying the subject-verb agreement errors in students’ speaking performance, finding out mostly the types of errors in applying the subject-verb agreement also finding out the source of errors made by the second-year students of English department of UNP. This research applied a descriptive qualitative research design with 28 students who participated in this study. The data of the research were collected through a test instrument. The test instrument covers a speaking test in a report form. All of the errors that were identified in subject-verb agreement were analyzing by using Surface Strategy Taxonomy introduced by Dulay et,al. the result of data analysis showed that the students contributed into four types of errors in subject-verb agreement’s term, they are (1) omission (38 errors / 25 %), (2) addition (47 errors / 27%). (3) misformation ( 76 / 45%), (4) misordering (10 errors / 6%). Furthermore, the research also found the sources of errors made by the students during his/her speaking report test, the frequent sources of errors are Intralingual transfer there are totally (100 errors / 57%), Interlingual transfer (45 errors / 25%), communication strategy ( 17 errors / 10 %) and the last one is context of learning ( 14 errors / 8%)